Work : a study in Australian society - Baker, Chris. (Nelson, 1989)
Work: A study in Australia society has been written specifically to meet the requirement of the new Australian Studies course, units 1 and 2, Work in Australian Society. The authors focus on work as it reflects Australian experiences and shapes Australian culture in a time of rapid economic and social change, and encourage students to explore a range of meanings for work.